Exploring University Student’s Experience of Self-Regulation and Mental Wellbeing in Context of Short Form Social Media Engagement: Investigating the Challenges: https://doi.org/10.55966/assaj.2025.4.1.040 - Dr. Iram Naz; Layba Murryam; Dr. Noreena Kausar (`, 2025)
The current qualitative work investigates how university students self-regulate and experience well-being when using short-form content engagement (SFCE) on social media platforms such as YouTube Shorts, TikTok and Instagram Reels. Fifteen participants (aged 19-27) were interviewed as part of a series of semi-structured interviews and data were analyzed using (Braun and Clarke’s 2006) systematic approach to thematic analysis. The deductive method was followed and informed by the literature of digital engagement and psychological well-being. Three key themes were noted: (1) Helix of Scrolling, representing the routine and immersive aspect of SFCE use; (2) Adrift or Docked Up, (3) paralleling how students were trying to control their utilization, either consciously or through inner battles; (3) Digital Comfort Zones, illustrating that SFC was both an emotional escape and a mental burden. Some students used active tactics such as app restrictions or mindful breaks, others said they felt overwhelmed or emotionally splintered. Results underscore the two-sided role of SFCE—both as coping and as a stressor—and emphasize the value of educational interventions promoting digital literacy and healthy online practices in the university students. Keywords: SFC (Short Form Content), Well-Being, Self-Regulation, Emotions, Reels, Engagement, SFCE (Short Form Content Engagement), Students